2022
DOI: 10.3390/ijms232112941
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Extracellular Vesicles Released by Leptin-Treated Breast Cancer Cells: A Potential Role in Cancer Metabolism

Abstract: Tumor extracellular vesicles (EVs), as endocytic vesicles able to transport nucleic acids, proteins, and metabolites in recipient cells, have been recognized fundamental mediators of cell-to-cell communication in breast cancer. The biogenesis and release of EVs are highly regulated processes and both the quantity of EVs and their molecular cargo might reflect the metabolic state of the producing cells. We recently demonstrated that the adipokine leptin, whose circulating levels correlate with adipose tissue ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Particularly, the increase in leptin secretion mediated by adipocytes can influence tumor cell metabolism, and also the metabolism of cells adjacent to the tumor 51 . For example, it has been shown that leptin influenced the protein cargo and the biological activity of extracellular vesicles secreted from breast cancer cells, increased mitochondrial metabolism of breast cancer cells, and also regulated macrophage metabolism, which are the most abundant immunological component in the tumor microenvironment 52 . Additionally, it has been demonstrated in estrogen receptor-positive (ER + ) cells, that leptin increased mitochondrial ATP production and enhanced mitochondrial respiration 53 – 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the increase in leptin secretion mediated by adipocytes can influence tumor cell metabolism, and also the metabolism of cells adjacent to the tumor 51 . For example, it has been shown that leptin influenced the protein cargo and the biological activity of extracellular vesicles secreted from breast cancer cells, increased mitochondrial metabolism of breast cancer cells, and also regulated macrophage metabolism, which are the most abundant immunological component in the tumor microenvironment 52 . Additionally, it has been demonstrated in estrogen receptor-positive (ER + ) cells, that leptin increased mitochondrial ATP production and enhanced mitochondrial respiration 53 – 55 .…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, autophagy is an easily-activated process that the cell uses to speed up nutrient bioavailability and satisfy the energetic demands required to sustain cancer features considered of a high energetic demand. Moreover, metabolic changes regulated by autophagy could influence the metabolism of non-tumor cells adjacent to the tumor, since it was suggested that leptin induced extracellular vesicle secretion with an important role in the metabolic crosstalk within the immune cells in the breast tumor microenvironment in which leptin concentration could be higher than in the blood 52 . This hypothesis needs to be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin, through Heat Shock Protein 90, is able to modulate the expression, at the post-transcriptional level, of the tumor susceptibility gene 101, known to be a key component of the endosomal sorting complex required for transport I [174]. Additionally, the same group reported that leptin affects the extracellular vesicle cargo, sustaining the expression of proteins mainly related to mitochondrial machinery and activity, thus modifying the behavior of recipient breast cancer cells and macrophages in terms of metabolism and energy production [175].…”
mentioning
confidence: 99%